Negative electrode material and preparation method and application thereof
By preparing the negative electrode material with a mesh conductive structure in lithium batteries, the expansion effect and low conductivity problems of silicon-based materials in lithium batteries are solved, and the cycle performance and service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411822262.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon-based anode materials have expansion effects and low conductivity in lithium batteries, resulting in insufficient cycling performance and service life of the battery.
Under the protection of an inert gas, diamine monomer, 2,5-diaminobenzenesulfonic acid and solvent are mixed to form a diamine mixture solution, and then react with diacid monomer and silicon-based material to form a sulfonic polyamide, and mixed with a carbon source for spray granulation and calcination, to prepare a negative electrode material with a network conductive structure.
This method effectively reduces the expansion effect of silicon material, improves the conductivity of the negative electrode material, and thus improves the circulation performance and service life of lithium batteries.
Smart Images

Figure BDA0005183368270000041 
Figure BDA0005183368270000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] As global environmental problems and energy crises become increasingly serious, new energy vehicles are the mainstream direction of future development. Among new energy vehicles, lithium batteries are their main power source. Lithium batteries have the advantages of high energy density, low cost and long service life.
[0003] Negative electrode materials are an important component of lithium batteries. The commonly used commercial negative electrode material is graphite, but the theoretical capacity of traditional graphite materials is low and cannot meet the battery's requirements for high energy density. Silicon has a high theoretical specific capacity, so it is a promising alternative to graphite. However, when silicon-based materials are used as negative electrode materials, the generation of Li4SiO4 and Li2O during the first lithium insertion process is an irreversible process. The generation of these substances consumes a large amount of lithium, resulting in a low initial coulombic efficiency of the battery. In addition, during the reaction between silicon and lithium, silicon-based materials have a large volume expansion effect, which causes the active material to pulverize and fall off during the battery cycle, reducing the battery's cycle performance and sharply reducing its service life.
[0004] Therefore, the existing negative electrode materials need to be improved. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a negative electrode material and a preparation method and application thereof, which effectively reduces the expansion effect of silicon material and improves the conductivity of the negative electrode material, thereby improving the cycle performance and service life of the battery.
[0006] In one aspect of the present invention, the present invention provides a method for preparing a negative electrode material. According to an embodiment of the present invention, the method comprises:
[0007] (1) under the protection of an inert gas, a diamine monomer, 2,5-diaminobenzenesulfonic acid and a solvent are mixed to obtain a diamine mixed solution;
[0008] (2) mixing the diamine mixed solution, the diacid monomer and the silicon-based material to obtain a sulfonic acid polyamide solution;
[0009] (3) mixing the sulfonic acid polyamide solution with a carbon source, and then spraying and granulating the mixture to obtain a carbonized precursor;
[0010] (4) calcining the carbonized precursor under an inert atmosphere to obtain a negative electrode material.
[0011] According to the method for preparing the negative electrode material of the embodiment of the present invention, a diamine monomer, 2,5-diaminobenzenesulfonic acid and a solvent are mixed to obtain a diamine mixed solution, and then a diacid monomer and a silicon-based material are added, and the diamine monomer, 2,5-diaminobenzenesulfonic acid and the diacid monomer undergo a polymerization reaction to generate a polyamide with a sulfonic acid group, and the silicon-based material is added thereto during the polymerization reaction, so that the surface of the silicon-based material is tightly coated with the sulfonic acid polyamide, and the sulfonic acid polyamide contains elements S and N. The silicon-based material can form a covalent bond with the elements S and N, thereby forming a mesh conductive structure, improving the coating effect, and reducing the expansion effect of the silicon material. Then a carbon source is added, and spray granulation is performed to obtain a precursor powder doped with carbon. The addition of carbon is beneficial to improving the conductivity of the negative electrode material. Then calcination is performed to generate a high temperature resistant negative electrode material.
[0012] In addition, the method for preparing the negative electrode material according to the above embodiment of the present invention may also have the following additional technical features:
[0013] In some embodiments of the present invention, in step (1), the molar ratio of the diamine monomer to 2,5-diaminobenzenesulfonic acid is (4-10):1, and the mass ratio of the diamine monomer to the organic solvent is 1:(3-10).
[0014] In some embodiments of the present invention, in step (1), the diamine monomer is one or more of p-phenylenediamine, m-phenylenediamine, 3,3'-dimethylbenzidine, 2,6-naphthalenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane and 1,2-ethylenediamine, and the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and acetonitrile.
[0015] In some embodiments of the present invention, in step (1), the diacid monomer is one or more of terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, adipic acid, azelaic acid, sebacic acid and furandicarboxylic acid or their derivatives, and the silicon-based material is one or more of silicon particles, silicon oxide and silicon dioxide.
[0016] In some embodiments of the present invention, the furandicarboxylic acid derivative is furandicarboxylic acid chloride.
[0017] In some embodiments of the present invention, the molar ratio of the diamine monomer to the diacid monomer is (1-2):1, and the mass ratio of the silicon-based material, the carbon source and the sulfonic acid polyamide solution is (1-9):(0.1-2):(0.1-0.5).
[0018] In some embodiments of the present invention, in step (3), the inlet air temperature of the spray granulation is 200-250°C, the outlet air temperature is 100-150°C, the feed rate is 0.4-0.8 L / h, and the carbon source is one or more of asphalt, glucose, phenolic resin and petroleum coke.
[0019] In some embodiments of the present invention, the calcination comprises: firstly heating the temperature to 260-300° C. and keeping the temperature for 1-5 hours, and then heating the temperature to 500-1000° C. and keeping the temperature for 1-5 hours.
[0020] In a second aspect of the present invention, the present invention provides a negative electrode material. According to an embodiment of the present invention, the negative electrode material is prepared by the above method. Thus, the negative electrode material effectively reduces the expansion effect of the silicon material, improves the conductivity of the negative electrode material, and thus improves the cycle performance and service life of the battery.
[0021] In a third aspect of the present invention, the present invention provides a negative electrode. According to an embodiment of the present invention, the negative electrode comprises the negative electrode material described above. Thus, the expansion effect of the negative electrode is low and the conductivity is improved.
[0022] In a fourth aspect of the present invention, the present invention provides a lithium battery. According to an embodiment of the present invention, the lithium battery comprises the above-mentioned negative electrode. Thus, the cycle performance and service life of the battery are improved.
[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0024] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0025] Example 1
[0026] Preparation of negative electrode materials:
[0027] (1) Under N2 protection, p-phenylenediamine, 2,5-diaminobenzenesulfonic acid and N,N-dimethylformamide are mixed to obtain a diamine mixed solution; wherein the molar ratio of p-phenylenediamine to 2,5-diaminobenzenesulfonic acid is 5:1, and the mass ratio of p-phenylenediamine to N,N-dimethylformamide is 1:4.
[0028] (2) mixing the obtained diamine mixed solution, furan dicarboxylic acid chloride and silicon particles to obtain a sulfonic acid polyamide solution; wherein the molar ratio of the diamine mixed solution to furan dicarboxylic acid chloride is 1.1:1, and the mass ratio of the silicon particles to the sulfonic acid polyamide solution is 1:0.2.
[0029] (3) mixing the obtained sulfonic acid polyamide solution with asphalt, wherein the mass ratio of asphalt to silicon particles is 0.2:2, and then spray granulating, with an inlet air temperature of 210° C., an outlet air temperature of 110° C., and a feed rate of 0.5 L / h to obtain a carbonized precursor;
[0030] (4) Under a N2 atmosphere, the obtained carbonized precursor was calcined by first heating the temperature to 260°C and keeping the temperature for 1 h, and then heating the temperature to 500°C and keeping the temperature for 1.5 h to obtain a negative electrode material.
[0031] Example 2
[0032] Preparation of negative electrode materials: The molar ratio of p-phenylenediamine to 2,5-diaminobenzenesulfonic acid is replaced with 10:1, the mass ratio of p-phenylenediamine to N,N-dimethylformamide is replaced with 1:9, the molar ratio of the diamine mixture to furandicarboxylic acid chloride is replaced with 2:1, the mass ratio of silicon particles to sulfonic acid polyamide solution is 1:0.5, the mass ratio of asphalt to silicon particles is 2:9, and the remaining process is the same as Example 1, and finally the negative electrode material is obtained.
[0033] Example 3
[0034] Preparation of negative electrode materials: The molar ratio of p-phenylenediamine to 2,5-diaminobenzenesulfonic acid is replaced with 7:1, the mass ratio of p-phenylenediamine to N,N-dimethylformamide is replaced with 1:6, the molar ratio of the diamine mixture to furandicarboxylic acid chloride is replaced with 1.6:1, the mass ratio of silicon particles to sulfonic acid polyamide solution is 5:0.3, the mass ratio of asphalt to silicon particles is 1:6, and the remaining process is the same as Example 1, and finally the negative electrode material is obtained.
[0035] Example 4
[0036] Preparation of negative electrode material: replacing p-phenylenediamine with m-phenylenediamine, replacing furan dicarboxylic acid chloride with isophthalic acid, replacing silicon particles with silicon monoxide, replacing asphalt with glucose, and the rest of the process is the same as Example 1, and finally obtaining the negative electrode material.
[0037] Example 5
[0038] Preparation of negative electrode material: replacing p-phenylenediamine with 4,4'-diaminodiphenyl ether, replacing furandicarboxylic acid chloride with furandicarboxylic acid, replacing silicon particles with silicon dioxide, and the rest is the same as in Example 1, and finally obtaining the negative electrode material.
[0039] Example 6
[0040] Preparation of negative electrode material: The calcination process was replaced by: first heating to 300° C. and keeping warm for 4 h, then heating to 900° C. and keeping warm for 4.5 h. The remaining process was the same as Example 1, and finally the negative electrode material was obtained.
[0041] Example 7
[0042] Preparation of negative electrode material: The inlet temperature of the spray granulation was replaced with an inlet temperature of 250°C, an outlet temperature of 150°C, a feed rate of 0.8 L / h, and the rest of the process was the same as in Example 1, and finally the negative electrode material was obtained.
[0043] Comparative Example 1
[0044] Preparation of negative electrode material: In this comparative example, after obtaining the diamine mixed solution, it is directly mixed with furan dicarbonyl chloride to obtain a sulfonic acid polyamide solution, which is then mixed with silicon particles and asphalt. The rest of the process is the same as in Example 1, and finally the negative electrode material is obtained.
[0045] Comparative Example 2
[0046] Preparation of negative electrode material: In this comparative example, silicon particles are directly mixed with asphalt, and the rest of the process is the same as Example 1, and finally a negative electrode material is obtained. The specific process is as follows: (1) Silicon particles are mixed with asphalt, wherein the mass ratio of asphalt to silicon particles is 0.2:2, and then spray granulation is performed, the inlet air temperature is 210°C, the outlet air temperature is 110°C, and the feed rate is 0.5L / h to obtain a carbonized precursor; under N2 atmosphere, the obtained carbonized precursor is calcined, first heated to 260°C and kept warm for 1h, and then heated to 500°C and kept warm for 1.5h to obtain a negative electrode material.
[0047] Performance Testing and Results
[0048] The negative electrode materials prepared in Examples 1-7 and Comparative Examples 1-2 were used to prepare pole pieces, and then button cells were assembled. Finally, the assembled button cells were subjected to electrochemical performance tests. The specific steps are as follows: the negative electrode materials prepared in Examples 1-7 and Comparative Examples 1-2 were mixed with styrene-butadiene rubber, conductive carbon black, and sodium hydroxymethyl cellulose in a mass ratio of 91:3:4:2, and then stirred evenly to obtain a coating slurry. The slurry was then coated on a copper foil current collector and dried in a vacuum oven to prepare a negative electrode.
[0049] A lithium sheet was used as a counter electrode, a glass fiber membrane was used as a separator, and a mixed solution of 1 mol / L lithium hexafluorophosphate and ethylene carbonate and dimethyl carbonate in an equal volume ratio was used as an electrolyte. The button cell was assembled in a vacuum glove box, and then the electrochemical performance was tested. The test results are shown in Table 1.
[0050] Test conditions: charge and discharge cycles at a rate of 0.1C, a voltage range of 0 to 1.5V, and a cycle number of 100. Finally, the battery after 100 cycles was disassembled and the expansion rate of the negative electrode was measured. The expansion rate data is shown in Table 1.
[0051] Table 1
[0052]
[0053]
[0054] It can be seen from the data in Table 1 that the battery prepared by the negative electrode material obtained by the present technical solution has a high first cycle reversible capacity, a high first coulomb efficiency, and a high capacity retention rate after 100 cycles, and the expansion rate of the pole piece is significantly reduced. It shows that the silicon-based material is added during the polymerization reaction, and the sulfonic acid polyamide can be more tightly coated on the silicon-based material. At the same time, the sulfonic acid polyamide contains elements S and N. The silicon-based material can form covalent bonds with the elements S and N, thereby forming a mesh conductive structure, reducing the expansion effect of the silicon material. The performance of the battery prepared by the negative electrode material obtained in Comparative Examples 1 and 2 is relatively poor. It can be seen from Comparative Example 1 that if the silicon particles are not added in the process of preparing the sulfonic acid polyamide, it is not conducive to reducing the volume expansion of the silicon particles. In Comparative Example 1, there is no generation of sulfonic acid polyamide, then the volume expansion effect of the negative electrode material is obvious, and the electrochemical performance in all aspects is relatively poor.
[0055] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0056] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: include: (1) under the protection of an inert gas, a diamine monomer, 2,5-diaminobenzenesulfonic acid and a solvent are mixed to obtain a diamine mixed solution; (2) mixing the diamine mixed solution, the diacid monomer and the silicon-based material to obtain a sulfonic acid polyamide solution; (3) mixing the sulfonic acid polyamide solution with a carbon source, and then spraying and granulating the mixture to obtain a carbonized precursor; (4) calcining the carbonized precursor under an inert atmosphere to obtain a negative electrode material.
2. The method for preparing a negative electrode material according to claim 1, characterized in that: In step (1), the molar ratio of the diamine monomer to 2,5-diaminobenzenesulfonic acid is (4-10):1, and the mass ratio of the diamine monomer to the organic solvent is 1:(3-10).
3. The method for preparing a negative electrode material according to claim 1, characterized in that: In step (1), the diamine monomer is one or more of p-phenylenediamine, m-phenylenediamine, 3,3'-dimethylbenzidine, 2,6-naphthalenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane and 1,2-ethylenediamine, and the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and acetonitrile; The diacid monomer is one or more of terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, adipic acid, azelaic acid, sebacic acid and furandicarboxylic acid or their derivatives, and the silicon-based material is one or more of silicon particles, silicon oxide and silicon dioxide.
4. The method for preparing a negative electrode material according to claim 3, characterized in that: The furandicarboxylic acid derivative is furandicarboxylic acid chloride.
5. The method for preparing a negative electrode material according to claim 1, characterized in that: The molar ratio of the diamine monomer to the diacid monomer is (1-2):1, and the mass ratio of the silicon-based material, the carbon source and the sulfonic acid polyamide solution is (1-9):(0.1-2):(0.1-0.5).
6. The method for preparing a negative electrode material according to claim 1, characterized in that: In step (3), the inlet air temperature of the spray granulation is 200-250°C, the outlet air temperature is 100-150°C, the feed rate is 0.4-0.8 L / h, and the carbon source is one or more of asphalt, glucose, phenolic resin and petroleum coke.
7. The method for preparing a negative electrode material according to claim 1, characterized in that: The calcination comprises: firstly heating the temperature to 260-300° C. and keeping the temperature for 1-5 hours, and then heating the temperature to 500-1000° C. and keeping the temperature for 1-5 hours.
8. A negative electrode material, characterized in that The negative electrode material is prepared by the method according to any one of claims 1 to 7.
9. A negative electrode, characterized in that: Comprising the negative electrode material according to claim 8.
10. A lithium battery, characterized in that: Comprising the negative electrode as claimed in claim 9.